Internalization of Staphylococcus aureus by endothelial cells induces cytokine gene expression. - Yao, L (1995)
The ability of the vascular endothelium to elaborate cytokines in response to gram-positive sepsis has received limited attention. This study examined cytokine expression by human umbilical vein endothelial cells (EC) following infection with a gram-positive bacterial pathogen, Staphylococcus aureus. S. aureus infection of EC resulted in the production of interleukin-6 (IL-6) and IL-1 beta. For IL-6, message was detected at 3 h after infection, protein was present at 24 h, and both message and protein persisted for 72 h. IL-1 beta message was detected at 12 h, IL-1 beta protein was detected at 24 h, and both persisted for 72 h. Message for colony-stimulating factor 1 remained unaltered. UV-killed S. aureus also elicited IL-1 beta and IL-6 message and protein expression at 24 and 48 h. Twenty-one clinical isolates of S. aureus were tested, and all induced IL-6 release by 48 h. However, the laboratory strain 8325-4 did not induce cytokine expression at any time point and was internalized by EC 1,000-fold less than other strains were. Internalization of latex beads by EC did not induce IL-6 gene expression. Furthermore, cytochalasin D treatment of the EC prevented IL-1 and IL-6 induction by S. aureus but not by tumor necrosis factor alpha or lipopolysaccharide. These results indicate that S. aureus is a potent inducer of IL-1 and IL-6 in EC and that internalization of S. aureus by EC is necessary for their cytokine expression. Thus, our data suggest that the vascular endothelium may play an important role in the pathogenesis of septicemia caused by gram-positive organisms.